Dyadic adjustment and sexual function in postmenopausal women (Annals of Medical Research, 2021)
Aim: To examine the dyadic adjustment and sexual function of postmenopausal women and the affecting individual factors. Material and Methods: This descriptive-correlational study was conducted with one-hundred thirty-nine postmenopausal women from October 2018 to May 2019 in Turkey. The data of the study was collected using an information form to determine the socio-demographic and gynecological characteristics of postmenopausal women, the Dyadic Adjustment Scale (DAS) and the Female Sexual Function Index (FSFI).Results: The 139 women completed the study. The mean score of DAS and FSFI were found 104.60±32.98 (0-151) and 12.71±9.48 (2-36), respectively, and a statistically significant positive relationship was found DAS and FSFI (p=0.000). There was a significant difference between income levels of women and the DAS scores (p=0.040). Additionally, it was found that the FSFI scores of the women having chronic disease were at lower levels (p=0.000).Conclusion: There was a significant positive correlation between dyadic adjustment and sexual function. Nevertheless, further studies are needed to test the effect of dyadic adjustment on sexual function in postmenopausal women.